The carnivorous rainbow plant Byblis filifolia Planch. secretes digestive enzymes in response to prey capture independently of jasmonates - Pavlovič, A; Jílková, T; Chamrád, I; Lenobel, R; Vrobel, O; Tarkowski, P (Plant biology (Stuttgart, Germany), 2025)
Carnivorous plants from the order Caryophyllales co-opted plant phytohormones from a group of jasmonates to regulate digestive enzyme activity. However, not all genera of carnivorous plants have been thoroughly explored, and the digestive physiology of Australian carnivorous rainbow plants of the genus Byblis (order Lamiales) is poorly understood. Here, we investigated the composition of digestive enzymes in the secreted fluid of Byblis filifolia using LC/MS, measured enzyme activity, and analysed tissue phytohormone levels after experimental feeding with fruit flies and coronatine application. Several hydrolytic digestive enzymes were identified in the secreted digestive fluid, the levels of which clearly increased in the presence of insect prey. However, in contrast to the sundew Drosera capensis, endogenous jasmonates do not accumulate, and coronatine, a molecular mimic of jasmonates, is unable to trigger enzyme secretion. Our results showed that B. filifolia is fully carnivorous, with its own digestive enzyme repertoire. However, in contrast to carnivorous genera from the Caryophyllales order, these enzymes are not regulated by jasmonates. This indicates that jasmonates have not been repeatedly co-opted to regulate digestive enzyme activity during the evolution of carnivorous plants.
Keywords: sundew; Animals; Carnivorous Plant; indeny; aminokyseliny; Drosera; digestive enzyme; Oxylipins; Carnivorous plant; regulátory růstu rostlin; phytohormones; Amino Acids; masožravé rostliny; Cyclopentanes; Caryophyllales; jasmonic acid; zvířata; Indenes; oxylipiny; Plant Growth Regulators; cyklopentany; Byblis